ANALYSIS OF FACTORS INFLUENCING THE USE OF INFORMATION TECHNOLOGY IN ACCOUNTING BY MSMES IN TANGERANG - Rina Ambarwati; Andika Mugi Gumilang; Ervina Yennie Permananingrum; Ahmad Pauji; Ilwin Hadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research aims to evaluate the factors influencing the use of accounting information technology by Micro, Small, and Medium Enterprises (MSMEs) in Tangerang. MSMEs play an important role in the Indonesian economy, but face challenges in efficient financial record-keeping and reporting. The use of accounting information technology can be a solution to improve the speed, accuracy, and transparency of financial transactions.The factors studied include accounting knowledge (X1), technology infrastructure (X2), perceived ease of use (X3), and management support (X4). This research uses a quantitative method with multiple linear regression analysis. The research population consists of all MSMEs in Tangerang City and Regency, with sampling conducted using a purposive sampling technique. Data was collected through a structured questionnaire with a five-point Likert scale. The analysis results show that accounting knowledge (X1) and management support (X4) significantly influence the use of accounting information technology (Y). However, technology infrastructure (X2) and perceived ease of use (X3) do not show a significant partial effect. Simultaneously, all four independent variables (X1, X2, X3, X4) have a significant influence on the use of accounting information technology (Y). The resulting regression model is: Y= 20.450+0.219X1+0.045X2+0.040X3+0.222X4. The coefficient of determination of 0.284 indicates that 28.4% of the variation in the use of accounting information technology is explained by the independent variables, while 71.6% is explained by other factors outside the model. This research is expected to help stakeholders formulate strategies to increase the adoption of accounting information technology in Tangerang MSMEs, thereby driving growth and competitiveness in the digital era.